Expression of D-serine and glycine transporters in the prefrontal cortex and cerebellum in schizophrenia. - Burnet, P; Hutchinson, L; von Hesling, M; Gilbert, E; Brandon, N; Rutter, A; Hutson, P; Harrison, P (2008)
The NMDA receptor co-agonists D-serine and glycine are thought to contribute to glutamatergic dysfunction in schizophrenia. They are removed from the synapse by specific neuronal and glial transporters, the status of which is clearly relevant to theories of D-serine and glycine function in the disorder. D-serine is primarily transported by Asc-1, and glycine by GlyT1 but maybe also by SNAT2. As a first step to addressing this issue, we studied Asc-1, GlyT1 and SNAT2 expression in dorsolateral prefrontal cortex and cerebellum of 18 subjects with schizophrenia and 20 controls, using immunoblotting and in situ hybridization. Asc-1 protein and SNAT2 mRNA were decreased in schizophrenia in both regions. GlyT1 mRNA and protein, and Asc-1 mRNA, were not altered. Antipsychotic administration for 14 days did not alter expression of the genes in rat brain. Unchanged GlyT1 suggests that glycine transport is not markedly affected in schizophrenia, and therefore that increased synaptic removal is not the basis for the putative deficit in glycine modulation of NMDA receptors in the disorder. Lowered Asc-1 in schizophrenia implies that D-serine reuptake is reduced, perhaps as a response to decreased synaptic D-serine availability. However, this interpretation remains speculative. Further investigations will be valuable in the evaluation of these transporters as potential therapeutic targets in psychosis.